THE INFLUENCE OF PERCEIVED DESIRABILITY, PERCEIVED FEASIBILITY, PERCEIVED ACCESSIBILITY TO DECISION TO CHOOSE THROUGH THE INTENTION TO CHOOSE OF POLITECHNIC IN EAST JAVA - susilo, kunto eko (Archives of Business Research, 2018)
ABSTRACT The government of Indonesia have attemped to encourage the growth of Polytechnic in Indonesia both public and private politechnic to anticipate the implementation of AFTA, but the phenomenon that occurs is various public perception of Polytechnics influence the decision to choose Polytechnic, especially in East Java. The study was conducted to examine the effect of Perceived Desirability, Perceived Feasibility, Perceived Accessibility to Decision To Choose Through Intention To Choose Polytechnic In East Java. There are 34,981 students of Polytechnic, with Slovin’s formula among 395 students were taken with proportional random sampling method from Students of Polytechnic in 10 cities in East Java. This explanatory research using Structural Equation Modeling (SEM) method to analyze data with AMOS Software, version 22. The data analysis with SEM resulted that Perceived Desirability has significant influence to intention to choose, Perceived feasibility has significant influence to intention to choose, Perceived accessibility hasn’t significant influence to intention to choose, and the last one is intention to choose a significant influence to the decision to choose. The hypothesis proved through data analysis with SEM, there are findings that Perceived accessibility hasn’t significant influence to intention to choose Polytechnic in East Java which isn’t in accordance with Hypothesis, and it can be interpreted that the tendency of Polytechnic Students in choosing Polytechnic isn’t supported by enabling environment factor of politechnic, the ability to access facilities and places, utilization of adequate facilities, and the development of politechnic infrastructure by the government. Keywords: Polytechnic, Perceived Desirability, Perceived feasibility, Perceived Feasibility, Perceived accessibility, intention to choose, decision to choose..